Point prevalence survey of antibiotic use in hospitals in Latin American countries - Levy Hara, G (2022)
Background: Point prevalence surveys (PPSs) on antibiotic use are useful for understanding different aspects related to prescription patterns in hospitals. Methods: An adaptation of the WHO methodology for a PPS on antibiotic use was applied. Hospital wards were divided into medical (MED), surgical (SUR), ICUs, gynaecology and obstetrics (GO), high-risk (HR) and mixed wards (MIX). A web application (RedCapVC ) through a mobile device was used for data collection. Results: Between December 2018 and August 2019, 5444 patients in 33 hospitals in five countries were included (10 hospitals in Cuba, 7 in Paraguay, 6 in El Salvador, 5 in Mexico and 5 in Peru). Of these patients, 54.6%received at least one antibiotic, with variations between and within hospitals and countries. Antibiotics were more frequently used in ICUs (67.2%), SUR (64.5%) and MED wards (54.2%), with 51.2% of antibiotics prescribed for community-acquired infections (CAIs), 22.9% for healthcare-associated infections (HAIs), 11.1% for surgical prophylaxis and 6.1% for unknown reasons. Adherence to guidelines was observed in 68.6% of cases (72.8% for CAIs, 72.4% for HAIs and 44.3% for prophylaxis). Third-generation cephalosporins were the class of antibiotics most frequently used (26.8%), followed by carbapenems (10.3%) and fluoroquinolones (8%). Targeted treatments were achieved in 17.3%of cases. Conclusions: Antibiotic use was generally higher than that published in other studies. There is an urgent need to promote and strengthen the antimicrobial stewardship programmes in Latin America.